Time-dependent mean-field investigations of the quasifission process - Umar A.S.; Simenel C.; Ayik S. (EPJ Web of Conferences, 2017)
We demonstrate that the microscopic Time-dependent Hartree-Fock (TDHF) theory provides an important approach to shed light on the nuclear dynamics leading to the formation of superheavy elements. In particular, we discuss studying quasifission dynamics and calculating ingredients for compound nucleus formation probability calculations. We also discuss possible extensions to TDHF to address the distribution of observables.